Determinan fenomena perubahan iklim dalam perspektif sosial ekonomi di Pulau Jawa dan Pulau Sumatera - Zufar Abdulmaajid Ramadhan; Zulfa Emalia (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2023)
The phenomenon of climate change has become a special concern throughout the world. This research was conducted to look at the determining factors from a social and economic perspective that can influence climate change on the Island of Java and Sumatera. The research is used panel data with a total of 80 research data in the 2018-2022. The variables used in the research were Average of Air Temperature, Gross Regional Domestic Product of Industrial Sector, Population Density, and Electrical Energy in Industrial Sector. The results of his research show that all independent variables GRDP of Industrial Sector, Population Density, and Electrical Energy in Industrial Sector have a significant and positive effect on the phenomenon of climate change on the Island of Java and Sumatera as viewed through the average of air temperature. Note: This article serves as a restored version of the original content following a corruption incident. The Digital Object Identifier (DOI) has been successfully re-registered and reactivated to ensure continued accessibility and citation integrity.